A COMPARATIVE STUDY OF PERFECT SOCIETY AND THE HUMAN IDEAL IN WORLD LITERATURE (American Journal of Research in Humanities and Social Sciences, 2024)
This article examines the representation of the ideal person and the perfect society in world literature, drawing on texts from various cultural and historical contexts. By analyzing seminal works such as Thomas More's Utopia and Plato's The Republic, alongside contemporary narratives from authors like Ursula K. Le Guin and Octavia Butler, we aim to highlight the diverse visions of utopia and the human ideal across global literature.